Conflict frames associated with state compulsory acquisition of lands in Barekese, Ghana - Owusu, Evans; Amoakoh, Alex Owusu (Frontiers in Sustainable Resource Management, 2025)
IntroductionCompulsory land acquisitions are commonly employed by many countries to serve broader public interests. Despite this, such acquisitions frequently lead to conflicts relating to compensation, transparency, and legitimacy of the public purpose. An understanding of stakeholder perspectives and framing strategies surrounding these acquisitions is essential to effectively address the resulting conflicts. This study investigates stakeholder perceptions and framing strategies underpinning the prolonged conflict resulting from Ghana's compulsory acquisition of land in 1965 for the construction of the Barekese dam.MethodsThe research employed a qualitative methodology involving key informant interviews, focus group discussions, and field observations. Data were analyzed through thematic analysis using NVivo software.ResultsFour primary conflict frames were identified: delayed crop compensation, unmet government promises, property destruction, and inaccurate documentation. Local communities emphasized themes of injustice, neglect, and betrayal, while government officials highlighted administrative and legal complexities. These incompatible frames have intensified mistrust and hindered effective conflict resolution.DiscussionThe findings indicate that divergent stakeholder perceptions and frames significantly impede constructive dialogue. Policymakers and practitioners should facilitate inclusive dialogue processes capable of reconciling these conflicting frames, thereby promoting more equitable and sustainable conflict resolutions.